COMPARATIVE ANALYSIS OF MEDICATION ASSORTMENT FOR CHRONIC OBSTRUCTIVE PULMONARY DISEASE TREATMENT PRESENTED AT UKRAINIAN AND POLISH PHARMACEUTICAL MARKETS - Onуshkiv О. І.; Lech I. Р.; Hroshovyi, T. A. (Фармацевтичний часопис, 2016)
COMPARATIVE ANALYSIS OF MEDICATION ASSORTMENT FOR CHRONIC OBSTRUCTIVE PULMONARY DISEASE TREATMENT PRESENTED AT UKRAINIAN AND POLISH PHARMACEUTICAL MARKETS О.І. Onуshkiv, I.Р. Lech, T. A. Hroshovyi I.Ya.HorbachevskyTernopilStateMedicalUniversity Summary: It was made a comparative study of Ukrainian and Polish pharmaceutical markets of medications used for treatment of chronic obstructive pulmonary disease. Also it was analyzed the structure of the assortment of the researched group due to the manufacturing countries, dosage forms and composition of active pharmaceutical ingredients and their origin. The results of market research can determine the main ways of domestic assortment improvement of medications studied at the pharmaceutical and therapeutic group. Keywords: medications for treatment of chronic obstructive pulmonary disease, the pharmaceutical market of Ukraine and Poland. Introduction. Nowadays, chronic obstructive pulmonary disease (COPD) is one of the biggest health problem. It is a major cause of morbidity and mortality in the world due to the medical, social and economic terms. Thus, according to the latest data of the World Health Organization, currently about 210 million people are suffering from COPD and more than 2.75 million people die of COPD each year. Late diagnosis and inappropriate treatment lead to incapacitation and early disability. After 10 years, every fourth ill patient with COPD becomes disabled. In accordance with the mentioned above information, comparative marketing analysis of medication assortment for the treatment of COPD are currently important at the domestic pharmaceutical market and at the market of Poland as one of the most developed markets of the European Union to determine the feasibility of developing new medications and the possibility to take the particular market field. Results and discussion. During the study it was used general rules for secondary collecting market information, methods of mathematical statistics. The information technologies are used for processing the results of the research. The analysis of the range of medication was done according to the classification of Anatomical Therapeutic Chemical (ATC) system using secondary information of electronic database of the State Registry of Medicines, Compendium, Pharmindex and data of information and analytical system «Baza leków DrWidget». The objects of the study were medications of R03 group «Medications used for the obstructive respiratory diseases» (according to the ATC classification): adrenergic medications for inhalation use (group R03A), inhaled asthma agents (group R03B), adrenergic medications for regular use (group R03C), other medications for regular use of the obstructive respiratory diseases (group R03D). Market research of medications for the treatment of COPD was performed on various parameters, including the manufacturing countries, dosage form and content of active pharmaceutical ingredients and their origin. Conclusions: 1. It was studied the medication assortment for COPD treatment listed on the pharmaceutical markets inUkraineandPoland. As a result of studies, it was found that the products in both countries are generally represented by foreign manufacturers, particularly inUkraine, their market share is 78.57 %, while inPoland– 80 %. 2. The market analysis data indicates that among foreign manufacturers of medication for COPD treatment at Ukrainian pharmaceutical market leading positions are occupied by 4 countries: the Great Britain, Spain, Poland and India; at the Polish market, the following countries are the leaders of medication delivery: the Great Britain, Germany, Switzerland and Israel. 3. The comparison of assortment represented at the pharmaceutical market ofUkraineandPolandon the dosage form indicates that the largest share has aerosols (23.81 %) at Ukrainian market and chewable tablets (29.57 %) at Polish. 4. The medication assortment for COPD treatment is represented only with synthetic drugs at both pharmaceutical markets, while the main group inUkraineis a group of medications based on montelukast, theophylline, budesonide, fluticasone and inPoland– montelukast, salbutamol, budesonide. References 1. Feshchenko Yu.I., Yashyna L.O., Potoczniak O.V. Chronic obstructive pulmonary disease and concomitant depression – an important medical and social problem // Ukrainian pulmonological journal. – 2013. – No.3. – P.56 – 58. – Access mode: http://www.ifp.kiev.ua/doc/journals/upj/13_dop/56.pdf 2. Tytova O.N. Clinical and pharmacoeconomic approaches for effective medical rehabilitation of patients disabled by chronic obstructive pulmonary disease: abstract of the thesis of the Candidate of Medical Sciences / O.N. Tytova – St. Pitersberg, 2008. – 25 p. 3. State Registry of Medicines of Ukraine. – [electronic version].– Access mode: http://www.drlz.kiev.ua/ 4. Pharmindex [ electronic version]. – Access mode: http://pharmindex.pl 5. Baza leków DrWidget [electronic version]. – Access mode: http://drwidget.pl/ 6. Compendium. – [electronic version].– Access mode: http://compendium.com.ua/